Anti-inflammatory activity of copao fruits (Eulychnia acida Phil., Cactacea) - Jiménez Aspee, Felipe (2014)
Copao (Eulychnia acida Phil., Cactacea) is an endemic species occurring in arid areas of northern Chile. The fruits are commercialized within the Elqui and Limari valleys, and are appreciated for its refreshing and acidic taste. A comparison of the anti-inflammatory effect of the enriched fruit phenolics from the pulp and epicarp was undertaken in samples from the Elqui and Limari valleys, main sources of supply and commercialization of the fruits. The anti-inflammatory activity of the XAD-copao extracts was assessed by the inhibition of the pro-inflammatory enzymes lipooxygenase (LOX) and cyclooxygenase (COX-1 and COX-2) in vitro at 100 μg extract/mL. The inhibitory capacity of LOX by extracts from the Limari valley was between 1.46-64.3% for pulp and 23.0-35.6% for epicarp. The COX-2 inhibition afforded values of 20.2-57.6% for pulp and 0-44% for epicarp. The COX-1 was not inhibited. For the Elqui valley samples, LOX inhibition ranged between 34.4-38.4% for pulp and 3.3-33.8% for epicarp. The COX-2 inhibition was between 0-27% for pulp and 1.1-39.9% for epicarp. The COX-1 inhibition ranged between 0-43% for pulp and 0-15.1% for epicarp. The main flavonoids found in this fruit are isorhamnetin-3-O-[α-rhamnopyranosyl-(16)-β-glucopyranoside] and quercetin-3-O-rutinoside1. Positive correlation was found between the anti-LOX activity and the content of rutin in pulp (R= 0.8235, p<0.05) and epicarp (R= 0.9120, p<0.05). Also, the anti-COX-2 activity and the content of isorhamnetin in epicarp showed a positive correlation (R=0.9422, p<0.01). The anti-inflammatory activity of isorhamentin and rutin have been reported2,3. The findings add value to the fruits as nutraceuticals. Acknowledgements: Financial support from FONDECYT project no. 1120096 and CONICYT-PCHA/Doctorado Nacional (2013-21130048) for F. Jiménez-Aspee is kindly acknowledged. References: 1Jimenez-Aspee et al. 2014. Food Res. Int. (62) 286-298.2 Pengfei et al. 2009. Plant Foods Hum Nutr (64) 141-145.3 Yang et al. 2013. Food Chem Toxicol (59) 362-379.